Gotong Royong Culture as an Alternative to Political Funding in Local Election - Siti Fatimah; Kushandajani Kushandajani; Fitriyah Fitriyah; Muhammad Adnan (Journal of Governance and Public Policy, 2023)
This research seeks to explore the phenomenon of gotong royong in political funding, which occurred in several districts/cities in Central Java during the election momentum used as one of the political funding strategies. This study uses the concept of campaign funds, and campaign expenditure as an analytical tool. Political funding has an important role because it intersects with many aspects of political activity. Indonesia as a pluralistic and multicultural nation has a variety of local wisdom, one of which is the culture of gotong royong. Especially, practices in the context gotong royong that occurred in Central Java's based political funding of Pilkada, which used as case study in this research. It can be optimised in social terms, and also in the political context. The result of this research is an alternative to political funding that raises public confidence to revive the values of gotong royong culture in building a more established democratic society. Based on the case studies studied, local wisdom-based election political funding alternatives were identified based on several factors. The first factor is building sustainability from the cultural value of gotong royong. Second, through cultural values that are built and then supported by mutual understanding communication among existing stakeholders to strengthen and preserve local wisdom-based political funding. Thirdly, it forms the political awareness of the community, the political awareness of the community that is formed will support candidates who really have the competence to solve regional problems.  This research uses a descriptive qualitative approach by observing the dynamics of gotong royong culture as an alternative to political funding which makes this study interesting to be researched more deeply.